EXPERIMENTAL RESEARCHES ON THE VEGETAL MATERIAL QUALITY, IN ORDER TO OPTIMIZE OF SOME PROCESSING PROCESSES OF THE MEDICINAL PLANTS - AUGUSTINA PRUTEANU; LADISLAU DAVID; VALENTIN VLADUT; ADRIANA MUSCALU (Journal of Engineering Studies and Research)
In the production of medicinal plants, the phytotherapeutic products quality is given by the content and the amount of bioactive substances from the plant. The quality of the phytotherapeutic products is dependent on the quality of the vegetal raw material as well as by the quality of the manufacturing processes. This paper presents the experimental determinations of some physical and dimensional properties of the vegetal material, in order to separate by sorts and of obtaining of some vegetal extracts therefrom. The determinations were performed in order to optimize the separation and extraction processes of medicinal plants. Knowing the characteristics of the vegetal material is particularly important for the achievement of some high-performance technical equipment for processing of medicinal plants.